Bell–like [Ga5] clusters in Sr3Li5Ga5: synthesis, crystal structure and bonding analysis. Issue 18 (16th July 2021) - Kotsch, Matthias; Prots, Yurii; Ormeci, Alim; Senyshyn, Anatoliy; Kohout, Miroslav; Grin, Yuri
Abstract: During the search for a possible replacement of the europium in the structure Eu3 Li5+x Ga5−x ( x  = 0.15) in order to facilitate the analysis of the chemical bonding in the bell–like [Ga5 ] clusters, the isostructural compound Sr3 Li5 Ga5 (space group R 3 ‾   m, a  = 9.6040(5) Å, c  = 22.061(1) Å) was discovered. A detailed investigation of the bonding situation in the first five–membered nonconvex Ga cluster utilizing the electron localizability approach became possible, revealing not only first signs of a transition from a Zintl to a Wade cluster, but also the presence of a [Sr6 ] polycation. Abstract :